Food security and conflict - Breisinger, Clemens; Maystadt, Jean-Francois (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by Clemens Breisinger, IFPRI and Jean-Francois Maystadt on 25 November 2013 in Brussels, Belgium.